Analisis Eksperimental Pengaruh Performa Aliran Natural (Tanpa Pengarah) dan Penggunaan Nozzle Pada Kincir Air Jenis Breastshot - Muhammad Helmi Kurniawan; Khusnul Khotimah Ayuningtiyas (Indonesian Journal of Engineering and Technology (INAJET), 2022)
Waterwheel is a means to convert water energy into mechanical energy in the form of torque at the wheel shaft. The waterwheel works with a large flow and utilizes a high waterfall. Currently waterwheels still have a small efficiency when compared to the existing water turbines. Therefore, further research is still needed to increase the rotation (rpm), mechanical power and efficiency of the waterwheel. The purpose of this study was to determine the performance of the nozzle angle variation with the natural flow of the waterwheel. In this study, using a breastshot type waterwheel with 12 blades with a water flow of 12 liters / second. By using the analysis, the results show that the mechanical data and the efficiency of the wheel are affected by the flow of water hitting the blade using a nozzle. The tilt angle of the nozzle is very important, the steeper the nozzle, the faster the water flow will hit the wheel blade. In the rotation test (rpm), the highest mechanical power and efficiency at the use of a nozzle with an angle of (25°) is at 76 rpm, which is 29 Watts and the lowest power is at 19 rpm, which is 13 Watts at a discharge of 12 liter / second. Whereas the natural flow is at the rotation 76 rpm which is equal to 7.11. Watt and the lowest power at the rotation 19 rpm namely 4 Watt at a discharge of 12 liter / second.